2008
DOI: 10.1172/jci36089
|View full text |Cite
|
Sign up to set email alerts
|

Neutrophil activation by the tissue factor/Factor VIIa/PAR2 axis mediates fetal death in a mouse model of antiphospholipid syndrome

Abstract: Women with antiphospholipid syndrome (APS), a condition characterized by the presence of antiphospholipid antibodies (aPL), often suffer pregnancy-related complications, including miscarriage. We have previously shown that C5a induction of tissue factor (TF) expression in neutrophils contributes to respiratory burst, trophoblast injury, and pregnancy loss in mice treated with aPL. Here we analyzed how TF contributes to neutrophil activation and trophoblast injury in this model. Neutrophils from aPL-treated mic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

18
175
0
4

Year Published

2009
2009
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 116 publications
(197 citation statements)
references
References 53 publications
18
175
0
4
Order By: Relevance
“…40,41 We previously demonstrated that pregnancy loss induced by antiphospholipid antibodies in mice is associated with increased TF expression. 16,20 In this study, we found increased TF expression and activity in placentas from CBA/J ϫ DBA/2 matings compared with control matings with normal pregnancies. Interestingly, we were able to translate the results obtained in mice in humans.…”
Section: Discussionsupporting
confidence: 48%
See 2 more Smart Citations
“…40,41 We previously demonstrated that pregnancy loss induced by antiphospholipid antibodies in mice is associated with increased TF expression. 16,20 In this study, we found increased TF expression and activity in placentas from CBA/J ϫ DBA/2 matings compared with control matings with normal pregnancies. Interestingly, we were able to translate the results obtained in mice in humans.…”
Section: Discussionsupporting
confidence: 48%
“…16,20 Day-15 placentas were frozen in OCT compound, cut into 10-m sections, and incubated with DHE (10 M) for 30 minutes at 37°C. Subsequently, the sections were washed and fluorescence images were obtained (Ex: 520, Em: 605 nm).…”
Section: Assessment Of Superoxide Production In Decidual Tissue By DImentioning
confidence: 99%
See 1 more Smart Citation
“…It is a specific, high-affinity receptor for factor (F)VII/VIIa and functions as a co-factor for FVIIa enzymatic activity. Activation of FVIIa triggers physiological blood coagulation and thrombosis, activates neutrophils through TF/FVIIa/proteinase-activated receptor-2 (PAR2) signalling and functions as an important mediator of C5a-induced oxidative burst in neutrophils in aPL-induced fetal injury (Redecha et al, 2007(Redecha et al, , 2008Boles & Mackman, 2010;Owens & Mackman, 2010).…”
Section: B2-glycoprotein I (B2gpi) and Its Receptors On The Cell Surfacementioning
confidence: 99%
“…A high prospective fetal loss rate was observed in untreated pregnancies of aPL-positive women with recurrent miscarriage, among whom the most common type of miscarriage is the first trimester loss of embryonic pregnancies (Rai et al, 1995). Both clinical and experimental observations suggest that pregnancy loss in these patients may involve an inflammatory response at the maternal-fetal interface, as well as disruption of normal trophoblast survival and function (Sebire et al, 2002;Bose et al, 2006;Redecha et al, 2007Redecha et al, , 2008. Mulla et al (2009) demonstrated for the first time that anti-b2GPI antibodies elicit a dose-dependent response in human first trimester trophoblast cells.…”
Section: Trophoblastsmentioning
confidence: 99%